2014
DOI: 10.1007/s12029-014-9672-1
|View full text |Cite
|
Sign up to set email alerts
|

The Descriptive Epidemiology of Gastric Cancer in Central America and Comparison with United States Hispanic Populations

Abstract: Purpose Delineate the epidemiology of gastric adenocarcinoma in Central America and contrast it with Hispanic-Latino populations in the U.S. Methods Published literature and Central America Ministry of Health databases were used as primary data sources, including national, population-based and hospital-based registries. U.S. data was obtained from the NCI-SEER registry. Incident gastric adenocarcinoma cases were analyzed for available data between 1985–2011, including demographic variables and pathology info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…In agreement with other studies, 12 37 the male to female ratio was 1.64 and GC was most common in the elderly. 12 38 Nevertheless, we found a high proportion of EOGC (14.7%) compared with those reported in most countries of the region, 38 only surpassed by Guatemala in Central America with national estimates of 16.5%, 12 a comparison worth noting even if our results are based on a single institution. Likewise, in a hospital-based study conducted in Mexico, a similar proportion of EOGC was reported.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with other studies, 12 37 the male to female ratio was 1.64 and GC was most common in the elderly. 12 38 Nevertheless, we found a high proportion of EOGC (14.7%) compared with those reported in most countries of the region, 38 only surpassed by Guatemala in Central America with national estimates of 16.5%, 12 a comparison worth noting even if our results are based on a single institution. Likewise, in a hospital-based study conducted in Mexico, a similar proportion of EOGC was reported.…”
Section: Discussionsupporting
confidence: 93%
“…Cases in which the endoscopic report could not be found in the clinical files were labelled as ‘unspecified’. 12 Histological type was based on the Lauren classification (intestinal, diffuse), 13 and mixed tumours were shown as a different category. 14 Tumour grade was categorised using ICD for Oncology, and clinical stage was based on the seventh edition of the TNM Staging System of the American Joint Committee on Cancer, taking into consideration the first staging reported in the clinical file by the physician at the NOI.…”
Section: Methodsmentioning
confidence: 99%
“…[7][8][9][10] Despite robust data on GAC and the role of HP from Asia, nearly all large studies in the United States have used national cancer databases, which contain limited demographic and environmental exposures, medical history, and, most importantly, no data on HP. [11][12][13][14][15][16] As a result, there are critical knowledge gaps in our understanding of the incidence of nonproximal GAC in the setting of HP in the United States, risk factors associated with future GAC, and the impact of HP treatment. Modeling studies have been performed to assess which populations in the United States may benefit from screening, but they were limited by a lack of robust data on the incidence of GAC in a US population.…”
mentioning
confidence: 99%
“…Nearly half of population in the CA‐4 resides in rural areas very similar to western Honduras, and our findings may be generalizable and helpful in the region. In addition, there is significant immigration to the United States from the CA‐4, and thus, our findings may have implications for patient care in the United States . In the treatment of H. pylori infection, resistance to clarithromycin and levofloxacin has been shown to be the central determinants of regimen efficacy.…”
Section: Discussionmentioning
confidence: 86%